(untitled) (American Journal of Business Management, Economics and Banking, 2026)
In today’s highly competitive business environment, traditional "Red Oceans" are becoming overcrowded, leading to shrinking profit margins. This article explores the application of "Blue Ocean Strategy" within large-scale corporations as a tool for sustainable growth through the creation of uncontested market spaces. The research utilizes qualitative analysis and case study methodologies, examining the strategic frameworks of global leaders that successfully transitioned from price-based competition to value innovation. The "Four Actions Framework" (Eliminate, Reduce, Raise, Create) is analyzed as the primary mechanism for strategic shifts. The study identifies that large corporations succeed in creating blue oceans not by focusing on technological breakthroughs alone, but by aligning innovation with utility, price, and cost positions. Findings suggest that organizations adopting this strategy can reduce marketing overheads by 15-20% while capturing untapped consumer segments. The article concludes that for large corporations, the mechanism of creating new markets requires a departure from benchmarking competitors toward "Value Innovation." This strategic pivot is essential for long-term dominance in the digital and globalized economy.